A case report of metastatic hepatocellular carcinoma in the mandible and coracoid process: A rare presentation. Issue 4 (January 2018) - Md Radzi, Ahmad Bakhtiar; Tan, Soek-Siam
Abstract: Rationale: We report a rare case of hepatocellular carcinoma (HCC) with metastases to the mandible and coracoid process of scapula without evidence of lung involvement. Patients concerns: The patient was diagnosed with HCC, presented 5 months later with right lower tooth pain, swelling over the right mandible area and right shoulder pain. Diagnoses: Histopathological examination of mandible showed findings suggestive of metastatic HCC. Magnetic resonance imaging (MRI) of the right shoulder revealed findings of irregular enhancing lesion at the right coracoid process causing erosion of the coracoid process. Interventions: Patient was subsequently referred for palliative medicine care. Outcomes: He received adequate analgesia. Lessons: Oral cavity and scapula metastases from HCC are very rare. Most oral metastases are associated with lung metastases, and they possibly occur by hematogenous route. In our case, the possible pathway of metastasis is an anastomotic network of paravertebral veins that bypasses the pulmonary, inferior caval, and portal venous circulations.